Histaminergic transmission slows progression of amyotrophic lateral sclerosis. Issue 4 (24th April 2019) - Apolloni, Savina; Amadio, Susanna; Fabbrizio, Paola; Morello, Giovanna; Spampinato, Antonio Gianmaria; Latagliata, Emanuele Claudio; Salvatori, Illari; Proietti, Daisy; Ferri, Alberto; Madaro, Luca; Puglisi‐Allegra, Stefano; Cavallaro, Sebastiano; et al.
Abstract: Background: Histamine is an immune modulator, neuroprotective, and remyelinating agent, beneficially acting on skeletal muscles and promoting anti‐inflammatory features in amyotrophic lateral sclerosis (ALS) microglia. Drugs potentiating the endogenous release of histamine are in trial for neurological diseases, with a role not systematically investigated in ALS. Here, we examine histamine pathway associations in ALS patients and the efficacy of a histamine‐mediated therapeutic strategy in ALS mice. Methods: We adopted an integrative multi‐omics approach combining gene expression profiles, copy number variants, and single nucleotide polymorphisms of ALS patients. We treated superoxide dismutase 1 (SOD1)‐G93A mice that recapitulate key ALS features, with the brain‐permeable histamine precursor histidine in the symptomatic phase of the disease and analysed the rescue from disease pathological signs. We examined the action of histamine in cultured SOD1‐G93A motor neuron‐like cells. Results: We identified 13 histamine‐related genes deregulated in the spinal cord of two ALS patient subgroups, among which genes involved in histamine metabolism, receptors, transport, and secretion. Some histamine‐related genes overlapped with genomic regions disrupted by DNA copy number and with ALS‐linked pathogenic variants. Histidine treatment in SOD1‐G93A mice proved broad efficacy in ameliorating ALS features, among which most importantly lifespan, motor performance, microgliosis, muscle atrophy, and motor neurons survival in vivo and in vitro . Conclusions: Our gene set/pathway enrichment analyses and preclinical studies started at the onset of symptoms establish that histamine‐related genes are modifiers in ALS, supporting their role as candidate biomarkers and therapeutic targets. We disclose a novel important role for histamine in the characterization of the multi‐gene network responsible for ALS and, furthermore, in the drug development process.